Inorganic-phase-rich double-layer SEI structure and regulation and control method thereof, negative electrode current collector activation method and battery
By modifying the end groups of the material on the negative electrode or negative current collector of the lithium metal battery and sodium metal battery, the inorganic phase-rich bilayer SEI structure is solved, and the battery performance degradation caused by lithium dendrites is achieved, and more uniform ion transmission and longer cycle life is achieved.
Patent Information
- Application Number
- CN202510085922.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-03-28
AI Technical Summary
Lithium metal batteries and sodium metal batteries cause uneven SEI layers due to the production of lithium dendrites, resulting in uneven lithium ion transmission, increasing the consumption of active lithium and electrolytes, reducing Coulomb efficiency and accelerated capacity attenuation.
The inorganic phase-rich bilayer SEI structure is adopted. This structure is generated by in situ targeting regulation of the end groups of the modified material on the negative electrode or the negative electrode current collector to realize the layered structure of the inorganic layer and the organic layer, enhance the lithium/sodium ion transfer rate and mechanical modulus, and inhibit dendrites' growth.
It achieves more uniform ion transmission and longer cycle life of lithium/sodium metal batteries, improves the balun efficiency and energy density of the battery, and extends the actual service life of the battery.
Smart Images

Figure CN119725374A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemistry, and relates to an inorganic phase-rich double-layer SEI structure and a regulation method thereof, a negative electrode current collector activation method and a battery. Background Art
[0002] Lithium metal has an ultra-high theoretical specific capacity (3860 mAh g -1 ) and low redox potential (-3.04 V vs SHE). At present, the development of commercial graphite-based negative electrode lithium-ion batteries has reached the theoretical limit. Lithium metal batteries (LMB) with lithium metal as the negative electrode are an important choice for future high-energy-density new energy batteries. Lithium metal batteries without negative electrodes have higher energy density. However, lithium metal has high reactivity and easily reacts with the electrolyte to form a solid electrolyte interface (SEI) with uneven composition and structure, resulting in uneven lithium ion transmission and aggravated growth of lithium dendrites. During the cycle, the generation of lithium dendrites will cause the SEI layer to continuously rupture and dynamically reconstruct, and continuously consume active lithium and electrolyte, thereby reducing coulombic efficiency and accelerating capacity decay, which seriously restricts the practical application of LMB. Sodium metal batteries and sodium metal batteries without negative electrodes have lower preparation costs than LMBs, but they also have similar application problems as lithium metal batteries.
[0003] To solve the above problems, people have made improvements in the negative electrode current collector modification design (such as porous structure, enhanced lithium affinity, and construction of modified protective layer) and electrolyte design (such as solvent optimization, lithium salt / sodium salt design, concentration control, and additive selection) of lithium, sodium and other metal batteries. Although the cycle stability of metal batteries has been improved to a certain extent, its coulombic efficiency is still difficult to reach a high and practical level, indicating that the side reactions of lithium / sodium metals have not been fundamentally blocked.
[0004] The solid electrolyte interface (SEI) acts as a barrier between metal and electrolyte. Its components and structure have important and most direct effects on the occurrence of side reactions at the interface, desolvation process, metal ion flux and deposition behavior. The components of SEI are mainly divided into organic components generated with organic solvents and inorganic components generated with inorganic anions. In comparison, inorganic components have higher ionic conductivity and higher mechanical modulus. Therefore, increasing the content of inorganic components in SEI can effectively enhance the lithium ion interface flux and inhibit dendrite growth. However, the types of lithium / sodium salts or additives that can be dissolved in large quantities by organic solvents and participate in the solvation structure are limited, resulting in very limited inorganic components that can be regulated. There is still a lack of systematic comparative studies on various inorganic components. In addition, the reduction process of lithium / sodium to anions and solvents in the electrolyte is inherently random and uncontrollable, which makes the generated SEI components unevenly distributed and have different properties, and it is impossible to inhibit dendrite growth and side reactions in the long term. Therefore, developing methods that can widely and controllably regulate SEI components and structures to achieve the purpose of rationally designing SEI components and structures is the most effective means to improve the cycle life of metal batteries. Summary of the invention
[0005] The present invention aims at the technical problems existing in SEI components and structures, and provides an inorganic phase-rich double-layer SEI structure. The SEI structure breaks through the traditional SEI mosaic structure, and the homogeneous distribution of the SEI components makes the ion transmission flux more uniform, induces the uniform deposition of lithium / sodium metal, and fundamentally inhibits the generation of dendrites. The SEI structure is generated by in-situ targeted regulation of the end groups of the modified materials on the negative electrode or the negative electrode current collector, and by simultaneously modifying different types of end groups in the modified materials, the composite of different inorganic components is achieved during the in-situ growth of the inorganic layer, thereby achieving multiple excellent properties such as high ionic conductivity and high mechanical modulus.
[0006] To achieve the above object, the present invention adopts the following technical solutions: In the first aspect, the present invention provides an inorganic-rich double-layer SEI structure, wherein the double-layer SEI structure grows on a negative electrode current collector or a metal negative electrode, and includes an inorganic layer and an organic layer, wherein the inorganic layer is located between the negative electrode current collector or the metal negative electrode and the organic layer, and the content of the inorganic layer is greater than the content of the organic layer. That is to say, the inorganic-rich double-layer SEI structure is dominated by inorganic components, the inorganic layer is close to the negative electrode current collector or the negative electrode material side, and the organic layer is close to the electrolyte side in the battery, wherein the negative electrode current collector can be Cu foil, aluminum foil, or other commonly used current collectors on batteries, and the metal negative electrode can be lithium foil, sodium foil, etc.
[0007] In the above technical solution, the cation in the inorganic layer component is Li + Or Na + , the anion is F - , Cl- Br - ,I - , O 2- , S 2- 、Se 2- 、N 3- or P 3- One or more of .
[0008] In a second aspect, the present invention provides a method for regulating the inorganic-rich double-layer SEI structure on a metal negative electrode or a negative electrode current collector, comprising the following steps: 1) preparing a slurry containing a terminal group-rich modification material, a binder, and a solvent, and then coating the slurry on a metal negative electrode or a negative electrode current collector to obtain a modified metal negative electrode or a negative electrode current collector; 2) The modified metal anode or anode current collector is used as the working electrode to assemble into a half-cell, and the current density, surface capacity density and cut-off voltage are set for deposition and stripping. During this period, the cations and anions dissociate, desolvate and first react with the organic macromolecules in the electrolyte to form an organic phase. Then, when the battery potential is close to 0 V, the cations reach the metal anode or anode current collector, spontaneously react with the end groups on the modified material and directly generate an inorganic phase in situ on the metal anode or anode current collector, that is, a double-layer SEI structure rich in inorganic phase is formed on the metal anode or anode current collector.
[0009] The binder used in preparing the coating slurry can be polyvinylidene fluoride (PVDF) or other commonly used binders in batteries. The solvent can be N-methylpyrrolidone (NMP) or other commonly used solvents in batteries. When the modified negative electrode current collector is used to assemble a negative electrode-free lithium metal battery or a negative electrode-free sodium metal battery, the modified negative electrode current collector needs to be activated in advance to generate an inorganic phase-rich double-layer SEI structure. The activation method refers to the above-mentioned regulation method. When the impedance value of the SEI structure is measured and remains unchanged, it means that the end group has been consumed and the activation is terminated. When the modified metal negative electrode is used to assemble a lithium metal battery or a sodium metal battery, there is no need to activate the negative electrode material in advance. During the battery cycle test, an inorganic phase-rich double-layer SEI structure will be generated in situ, and a double-layer SEI structure will generally be generated in the first 5 cycles of the cycle test.
[0010] In the above technical solution, the end group-rich modification material is an end group-rich MXene material, a carbon material or a conductive polymer.
[0011] In the above technical solution, the terminal group is selected from one or more of -F, -Cl, -Br, -I, -O, -S, -Se, -N or -P.
[0012] In the present invention, the MXene material can be the common Ti3C2T xThe carbon material can be carbon fiber, carbon nanotube or graphene, the conductive polymer can be polyaniline (PANI), polypyrrole (PPy), polythiophene, polydopamine (PDA), etc., and the MXene material, carbon material or conductive polymer can all be made to contain the above-mentioned specific end groups by corresponding methods. For example, the MXene material adopts the high-energy electric shock method disclosed in patent CN118239488A.
[0013] That is, the cation species in the inorganic phase of the double-layer SEI structure of the present invention depends on the cation species in the battery (such as Li + 、Na + ), the anion depends on the type of end group on the modified material, and the organic phase component depends on the electrolyte composition. The present invention can achieve precise control of the inorganic phase component by adjusting the type of end group on the modified material, and can also achieve the composite of different inorganic components when the inorganic layer is grown in situ by simultaneously modifying different types of end groups in the modified material.
[0014] In a third aspect, the present invention provides a method for activating a negative electrode current collector of a battery based on the above-mentioned inorganic phase-rich double-layer SEI structure, comprising the following steps: 1) preparing a slurry containing a terminal group-rich modification material, a binder, and a solvent, and then coating the slurry on a negative electrode current collector to obtain a modified negative electrode current collector; 2) The modified current collector is used as the working electrode and assembled into a half-cell. The current density and surface capacity density are set for deposition and stripping. During this period, the cations and anions dissociate, desolvate, and first react with the organic macromolecules in the electrolyte to form an organic phase. Then the cations reach the negative electrode current collector, spontaneously react with the end groups on the modified material, and directly generate an inorganic phase in situ on the negative electrode current collector, thereby forming an inorganic phase-rich double-layer SEI structure on the negative electrode current collector. The activation is terminated when the impedance value of the SEI structure is measured to be unchanged.
[0015] In a fourth aspect, the present invention provides a lithium metal battery comprising a positive electrode, a negative electrode, an electrolyte and a separator, wherein a modifying material rich in end groups is coated on the metal negative electrode, and an inorganic phase-rich double-layer SEI structure is generated in situ during the battery cycle test.
[0016] In a fifth aspect, the present invention provides a negative electrode-free lithium metal battery, comprising a lithiated positive electrode, a negative electrode, an electrolyte and a separator, wherein a modification material rich in end groups is coated on the negative electrode current collector, and an inorganic phase-rich double-layer SEI structure is generated in situ after activation.
[0017] In a sixth aspect, the present invention provides a sodium metal battery comprising a positive electrode, a negative electrode, an electrolyte and a separator, wherein a modifying material rich in end groups is coated on the metal negative electrode, and an inorganic phase-rich double-layer SEI structure is generated in situ during the battery cycle test.
[0018] In the seventh aspect, the present invention provides a negative electrode-free sodium metal battery, including a sodium-containing positive electrode, a negative electrode, an electrolyte and a separator, wherein the negative electrode current collector is coated with a modification material rich in end groups, and an inorganic phase-rich double-layer SEI structure is generated in situ after activation.
[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention utilizes a modifying material rich in end groups to modify the negative electrode current collector, and generates an inorganic phase-rich double-layer SEI structure in situ on the metal negative electrode or the negative electrode current collector through an electrochemical reaction. The SEI structure breaks through the traditional SEI mosaic structure, has a faster lithium / sodium ion transmission rate and a higher mechanical modulus, and induces uniform deposition of lithium / sodium metal. The double-layer structure of the inorganic phase and the organic phase is more conducive to exerting the high mechanical modulus of the inorganic phase and the viscoelasticity of the organic phase, and also inhibits dendrite growth during a long cycle, thereby improving the coulombic efficiency of the battery and extending its cycle life.
[0020] 2. The inorganic layer in the double-layer SEI structure of the present invention is located between the negative electrode current collector or the metal negative electrode and the organic layer. The dense inorganic layer prevents the continuous side reaction of lithium / sodium metal and the electrolyte, reduces the loss of active substances, and prolongs the cycle life of the lithium / sodium metal battery. At the same time, by simultaneously modifying different types of end groups in the modified material, the composite of different inorganic components can be achieved during the in-situ growth of the inorganic layer, thereby achieving multiple excellent properties such as high ionic conductivity and high mechanical modulus.
[0021] 3. Lithium / sodium metal batteries and negative electrode-free lithium / sodium metal batteries using metal negative electrodes or current collectors containing inorganic phase-rich double-layer SEI structures have faster ion transfer efficiency, and their pole pieces have better reversibility. During the cycle, the polarization potential of the battery is lower, and the battery has a longer cycle life. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the X-ray diffraction spectrum of the Cu@Ti3C2-O negative electrode current collector prepared in Example 1.
[0023] Figure 2 This is the CV curve of the first five cycles of the Cu@Ti3C2-O||Li half-cell of Example 3.
[0024] Figure 3 This is a cryo-TEM high-resolution image of the Li2O-SEI structure obtained in Example 3 and its corresponding Fourier transform image.
[0025] Figure 4 The X-ray photon diffraction full spectrum and O 1s and Li 1s fine orbital spectra of LiF-SEI obtained in Example 3.
[0026] Figure 5 The X-ray photon diffraction full spectrum and Cl 1s and Li 1s fine orbital spectra of LiCl-SEI obtained in Example 3 are shown.
[0027] Figure 6 The X-ray photon diffraction full spectrum and Br 3d and Li 1s fine orbital spectra of LiBr-SEI obtained in Example 3 are shown.
[0028] Figure 7 The X-ray photon diffraction full spectrum and I 3d and Li 1s fine orbital spectra of LiI-SEI obtained in Example 3.
[0029] Figure 8 The X-ray photon diffraction full spectrum and O 1s and Li 1s fine orbital spectra of Li2O-SEI obtained in Example 3.
[0030] Fig. 9 The X-ray photon diffraction full spectrum and S 2p and Li 1s fine orbital spectra of Li2S-SEI obtained in Example 3.
[0031] Fig.10 The X-ray photon diffraction full spectrum and Se 3d and Li 1s fine orbital spectra of Li2Se-SEI obtained in Example 3.
[0032] Fig.11 The X-ray photon diffraction full spectrum and N 1s and Li 1s fine orbital spectra of Li3N-SEI obtained in Example 3.
[0033] Fig.12 The X-ray photon diffraction full spectrum and P 2p and Li 1s fine orbital spectra of Li3P-SEI obtained in Example 3.
[0034] Fig.13 This is a pie chart showing the X-ray photon diffraction component content distribution of LiI-SEI obtained in Example 3.
[0035] Fig.14 The Cu@Ti3C2-O in Example 3 deposited 3 mAh cm after 20 cycles. -2 SEM image of the surface capacity after lithium deposition.
[0036] Fig.15 Atomic force microscopy DMT modulus distribution images of the mosaic SEI and Li2O-SEI obtained in Example 3.
[0037] Fig.16 This is a test diagram of the cycle performance of a half-cell assembled with Cu@Ti3C2-X negative electrode current collector and copper foil in Example 4.
[0038] Fig.17The Li obtained by assembling the half-cell of Example 4 and conducting the AC impedance test + Fitting and comparison of activation energies required for transport through the SEI.
[0039] Fig.18 X-ray photon diffraction C 1s, O 1s and Li 1s fine orbital spectra of the Li2O-SEI formed on the negative electrode of Example 5.
[0040] Fig.19 This is the cycling performance test diagram of the symmetrical batteries Li@Ti3C2-O||Li@Ti3C2-O, Li||Li and Li-LiNO3||Li-LiNO3 assembled in Example 5.
[0041] Fig. 20 This is a long cycle performance test diagram of a full battery assembled with a Li@Ti3C2-O substrate and a lithium sheet in Example 6.
[0042] Fig.21 This is a long cycle performance test diagram of Example 7, in which a negative electrode-free lithium metal battery is assembled using a Cu@Ti3C2-O substrate and a Cu foil. DETAILED DESCRIPTION
[0043] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Unless otherwise specified, the technical means used in the examples are conventional means known to those skilled in the art. The test methods in the following examples are conventional methods unless otherwise specified.
[0044] Example 1 Preparation of Cu@Ti3C2-X negative electrode current collector modified with different end group modification materials MXene materials with -F, -Cl, -Br, -I, -O, -S, -Se, -N, and -P end groups (Ti3C2-F, Ti3C2-Cl, Ti3C2-Br, Ti3C2-I, Ti3C2-O, Ti3C2-S, Ti3C2-Se, Ti3C2-N, and Ti3C2-P) and PVDF binder were dissolved in NMP solvent in a mass ratio of 9:1, and the slurry was obtained after sufficient stirring. The slurry was coated on a Cu foil substrate with a scraper to a thickness of 50 µm. After vacuum drying at 80 °C, it was taken out and cut into pole pieces with a diameter of 10 mm to obtain the modified Cu@Ti3C2-X negative electrode current collectors, which were respectively recorded as Cu@Ti3C2-F, Cu@Ti3C2-Cl, Cu@Ti3C2-Br, Cu@Ti3C2-I, Cu@Ti3C2-O, Cu@Ti3C2-S, Cu@Ti3C2-Se, Cu@Ti3C2-N and Cu@Ti3C2-P.
[0045] Figure 1This is the X-ray diffraction spectrum of the Cu@Ti3C2-O negative electrode current collector prepared in Example 1. It can be seen in the figure that there are three obvious characteristic peaks of the Cu substrate at 43.3°, 50.4° and 74.1°, respectively. In addition, 6.9°, 14.7° and 22.4° correspond to the (002), (004) and (006) crystal planes of Ti3C2-O, respectively, indicating that Example 1 has successfully modified the Ti3C2-O MXene material on the Cu foil substrate.
[0046] Example 2 Preparation of Li@Ti3C2-X negative electrode modified with different end group modification materials MXene materials with -F, -Cl, -Br, -I, -O, -S, -Se, -N, and -P end groups (Ti3C2-F, Ti3C2-Cl, Ti3C2-Br, Ti3C2-I, Ti3C2-O, Ti3C2-S, Ti3C2-Se, Ti3C2-N, and Ti3C2-P) and PVDF binder were dissolved in NMP solvent in a mass ratio of 9:1, and the slurry was obtained after sufficient stirring. The slurry was coated on a Li foil substrate with a scraper to a thickness of 50 µm. After drying in an Ar atmosphere, it was taken out and cut into pole pieces with a diameter of 10 mm to obtain the modified Li@Ti3C2-X negative electrodes, which were respectively recorded as Li@Ti3C2-F, Li@Ti3C2-Cl, Li@Ti3C2-Br, Li@Ti3C2-I, Li@Ti3C2-O, Li@Ti3C2-S, Li@Ti3C2-Se, Li@Ti3C2-N, and Li@Ti3C2-P.
[0047] Example 3 The Cu@Ti3C2-F, Cu@Ti3C2-Cl, Cu@Ti3C2-Br, Cu@Ti3C2-I, Cu@Ti3C2-O, Cu@Ti3C2-S, Cu@Ti3C2-Se, Cu@Ti3C2-N and Cu@Ti3C2-P negative electrode current collectors obtained in Example 1 were used as working electrodes, and lithium sheets with a diameter of 14 mm were used as counter electrodes and reference electrodes to assemble half cells. When assembling the cells, the electrolyte composition added was LiFSI. At a current density of 1 mA cm -2 , with an area capacity density of 1 mAh cm -2 The deposition was carried out under the condition of current density of 1 mA cm -2 , peeling is carried out under the condition of a cut-off voltage of 1 V. After 20 cycles, the stripping is terminated when the measured impedance value remains unchanged.
[0048] The Cu@Ti3C2-O||Li half-cell of Example 3 was charged at 0.2 mV s -1 The CV test was performed at a scanning speed of 10000. The CV curves of the first five circles are as follows: Figure 2 As shown, the voltage range is 0 V-OCV, and the lithium salt in the electrolyte dissociates in the voltage range of 1.0-1.5 V. + dissociate and complete the desolvation process, in the range of 0.5-1.0 V Li + The organic layer of SEI is formed by side reactions with anions and organic macromolecules. When it is close to 0 V, Li + When it reaches the substrate, it reacts with the end groups to form an inorganic layer. As the cycle progresses, the corresponding peaks of the CV curve weaken, and SEI is gradually formed. When the end group content is high, the formation process of the inorganic components of SEI will be prolonged. It can be seen that the formation of the inorganic components of SEI is lagging, and its aggregation position is between the substrate and the organic layer, and together with the organic layer, it forms a double-layer structure of SEI.
[0049] The Li2O-SEI structure obtained in Example 3 was subjected to cryo-electron microscopy (Cyro-TEM) test, and the results are as follows Figure 3 As shown, the left picture is a high-resolution transmission image of Li2O-SEI, and the thickness of the inorganic layer is significantly greater than that of the organic layer; the right pictures are the Fourier transform images corresponding to the double-layer structure, in which there are no obvious lattice fringes on the side of SEI close to the electrolyte, and there are no obvious crystal rings in the corresponding diffraction image. SEI has obvious lattice fringes on the side close to the substrate, and the lattice spacing measurement corresponds to Li2O (111) d=0.268 nm, Li2O (200) d=0.232 nm, and Li2O (220) d=0.164 nm, respectively, indicating that Ti3C2-O successfully regulates the composition and structure of SEI.
[0050] The LiF-SEI, LiCl-SEI, LiBr-SEI, LiI-SEI, Li2O-SEI, Li2S-SEI, Li2Se-SEI, Li3N-SEI and Li3P-SEI obtained in Example 3 were subjected to X-ray photon diffraction tests respectively. The full spectrum and fine spectrum of X-ray photon diffraction are shown in FIG. Figure 4 to Figure 12 The results show that the corresponding elements of the end groups in SEI can be detected from XPS, and the corresponding inorganic component signals can be detected in the Li 1s fine spectrum and F 1s, Cl 1s, Br 3d, I 3d, O 1s, S 2p, Se 3d, N 1s and P 2p fine spectra, indicating that the end groups on the current collector participate in the formation of the SEI structure and target the regulation of the inorganic components of SEI.
[0051] The components of the LiI-SEI obtained in Example 3 were analyzed and compared after X-ray photon diffraction test. Fig.13As shown. It can be seen that the lithium ions dissociate from the terminal group -I on the MXene material and the F - Two inorganic components, LiI and LiF, are generated, of which LiI and LiF account for 58.6% of the total, and LiI accounts for 55.8% of all inorganic components. This shows that the LiI-SEI structure obtained by Ti3C2-I regulation is dominated by inorganic substances, and LiI corresponding to the end group accounts for more than half of all inorganic components.
[0052] The Cu@Ti3C2-O anode current collector in Example 3 deposited 3 mAh cm after 20 cycles. -2 The electrode with surface capacity lithium was removed and observed under electron microscope to obtain the deposition morphology and cross-sectional diagram. The results are as follows Fig.14 As shown in the left figure, a uniform layer of lithium is deposited on the surface of Cu@Ti3C2-O, and the cross-sectional view on the right shows that 3 mAh cm -2 The thickness of the deposited lithium is 31.5 µm.
[0053] The completely peeled-off electrode piece of the Cu@Ti3C2-O negative electrode current collector in Example 3 after 20 cycles was removed for atomic force microscope DMT modulus test. The test results are as follows: Fig.15 Compared with the traditional mosaic SEI (left), the Li2O-SEI (right) has an average surface modulus of 12.07 GPa, which has a better effect in inhibiting dendrite growth.
[0054] Example 4 The Cu@Ti3C2-F, Cu@Ti3C2-Cl, Cu@Ti3C2-Br, Cu@Ti3C2-I, Cu@Ti3C2-O, Cu@Ti3C2-S, Cu@Ti3C2-Se, Cu@Ti3C2-N and Cu@Ti3C2-P negative electrode current collectors obtained in Example 1 were used as working electrodes, lithium sheets were used as counter electrodes and reference electrodes, and the separator was a PP composite separator to assemble into half-cells. When assembling the battery, the electrolyte component added was LiFSI, and a CR2032 battery shell was selected. After assembly, it was compacted on a tablet press and electrochemical tests were performed after standing for a certain period of time.
[0055] The half-cell assembled in Example 4 was tested for cycle performance, and the half-cell assembled with copper foil current collector was used as a control. The results are as follows: Fig.16 The results show that at a current density of 1 mA cm -2 , with an area capacity density of 1 mAh cm -2 The deposition was carried out under the condition of current density of 1 mA cm -2, the stripping was carried out under the condition of a cut-off voltage of 1 V. Cu@Ti3C2-I can still maintain a Coulombic efficiency of 98% after 420 cycles, Cu@Ti3C2-O can still maintain a Coulombic efficiency of 98% after 250 cycles, and Cu@Ti3C2-N can still maintain a Coulombic efficiency of 98% after 350 cycles. In contrast, Cu foil can only be cycled 50 times, and its Coulombic efficiency is also unstable.
[0056] After the half-cells of Cu@Ti3C2-F||Li, Cu@Ti3C2-Cl||Li, Cu@Ti3C2-Br||Li, Cu@Ti3C2-I||Li, Cu@Ti3C2-O||Li, Cu@Ti3C2-S||Li, Cu@Ti3C2-Se||Li, Cu@Ti3C2-N||Li, and Cu@Ti3C2-P||Li of Example 4 were cycled for 20 times, after the SEI was formed, AC impedance tests were performed at different temperatures and R was fitted. SEI The impedance value of Li is calculated by fitting the Arrhenius equation. + The activation energy Ea of passing through SEI is as follows Fig.17 As shown. It can be seen that Li + The Ea through Li2O-SEI is only 32.06 KJ mol -1 The Ea of Li3N-SEI is also low, only 35.95 KJ mol -1 .
[0057] Example 5 The negative electrodes of Li@Ti3C2-F, Li@Ti3C2-Cl, Li@Ti3C2-Br, Li@Ti3C2-I, Li@Ti3C2-O, Li@Ti3C2-S, Li@Ti3C2-Se, Li@Ti3C2-N and Li@Ti3C2-P obtained in Example 2 were assembled on both sides of the PP separator, and 1 mol / L LiFSI was added as the lithium salt and DME was used as the solvent electrolyte, or 1 mol / L LiFSI, DME as the solvent and 2 wt% LiNO3 as the additive electrolyte, to assemble into a symmetrical battery. The battery shell selected was CR2032, which was compacted on a tablet press after assembly and electrochemical testing was performed after standing for a period of time.
[0058] The symmetrical battery assembled with Li@Ti3C2-O negative electrode was disassembled after 5 cycles, and the Li2O-SEI formed on the negative electrode was tested by X-ray photon diffraction. The X-ray photon diffraction fine spectrum is shown in Fig.18The results show that the presence of Li2O signals (52.3 eV and 528.3 eV) can be detected in both the Li 1s and O1s fine spectra, indicating that the end groups of the modified materials on the lithium foil participate in the formation of the Li2O-SEI structure and target the regulation of the inorganic components of the SEI.
[0059] The symmetrical cells Li@Ti3C2-O||Li@Ti3C2-O, Li||Li and Li-LiNO3||Li-LiNO3 assembled in Example 5 (the first two symmetrical cells used 1 mol / L LiFSI as electrolyte and DME as solvent, and the last one used 1 mol / L LiFSI as electrolyte, DME as solvent and 2 wt% LiNO3 as additive) were tested for long cycle performance. The results are as follows Fig.19 As shown. It can be seen that the symmetrical battery assembled by Li@Ti3C2-O has a high -2 Current density, 3 mAh cm -2 Under the condition of low capacity density, it can be cycled for nearly 1500 h, while the cycle life of Li-LiNO3||Li-LiNO3 is close to 1000 h, and that of Li||Li is only 500 h, which shows that Li2O-SEI can make lithium metal deposit evenly during long cycles and has a better effect in inhibiting dendrites.
[0060] Example 6 The positive electrode material NCM90, the conductive agent SuperP and the binder PVDF were coated on the aluminum foil in a mass ratio of 9:0.5:0.5, and cut into 10 mm pole pieces by a cutting machine as the positive electrode of the whole battery. Li@Ti3C2-F, Li@Ti3C2-Cl, Li@Ti3C2-Br, Li@Ti3C2-I, Li@Ti3C2-O, Li@Ti3C2-S, Li@Ti3C2-Se, Li@Ti3C2-N, and Li@Ti3C2-P prepared in Example 2 were used as the negative electrodes, the diaphragm was a PP mixed diaphragm, and a CR2025 battery shell was selected. It was compacted on a tablet press and the electrochemical performance test was carried out after standing for a period of time.
[0061] In Example 6, Li@Ti3C2-O and Li were assembled into full cells at 0.5 A g -1 The long cycle performance test was carried out at a current density of Fig. 20 As shown. It can be seen that when using Li@Ti3C2-O negative electrode, at 0.5 A g -1 The initial capacity at the current density is 202.18 mAh g -1 After 90 cycles, the capacity is 190.00 mAh g -1The capacity retention rate is 93.9%. In contrast, when using Li foil, the initial capacity density of the battery is 209.51 mAh g -1 , the capacity after 90 cycles is 136.00 mAh g -1 The above test results further show that Li@Ti3C2-O has excellent long-cycle stability, thanks to the fast lithium ion transfer rate of Li2O-SEI, which induces more uniform lithium metal deposition. At the same time, the Li2O inorganic layer in Li2O-SEI blocks the side reaction between lithium metal and electrolyte, reducing the loss of active lithium. Its high mechanical modulus also effectively inhibits the growth of dendrites during the cycle.
[0062] Example 7 The positive electrode material NCM90, conductive agent SuperP and binder PVDF were coated on aluminum foil in a ratio of 9:0.5:0.5, and cut into 10 mm pole pieces by a cutting machine as the positive electrode of the whole battery. Cu@Ti3C2-F, Cu@Ti3C2-Cl, Cu@Ti3C2-Br, Cu@Ti3C2-I, Cu@Ti3C2-O, Cu@Ti3C2-S, Cu@Ti3C2-Se, Cu@Ti3C2-N, and Cu@Ti3C2-P were used as negative electrodes, and the separator was a PP mixed separator. CR2025 battery shell was selected, compacted on a tablet press, and the electrochemical performance was tested after standing for a period of time.
[0063] In Example 7, Cu@Ti3C2-O and Cu were used to assemble a negative electrode-free lithium metal battery at 0.5 A g -1 The long cycle performance test was carried out at a current density of Fig.21 When using Cu@Ti3C2-O substrate, at 0.5 A g -1 The initial capacity at the current density is 153.14 mAh g -1 After 50 cycles, the capacity is 89 mAh g -1 The capacity retention rate is 42.4%. In contrast, when using Cu foil, the initial capacity density of the battery is 138.40 mAh g -1 The capacity after 50 cycles is 48.77 mAh g -1 The above test results further show that Cu@Ti3C2-O has excellent long-cycle stability, thanks to the fast lithium ion transfer rate of Li2O-SEI, which induces more uniform lithium metal deposition. At the same time, the Li2O inorganic layer in Li2O-SEI blocks the side reaction between lithium metal and electrolyte, reducing the loss of active lithium. Its high mechanical modulus also effectively inhibits the growth of dendrites during the cycle.
[0064] The embodiments described above are only preferred embodiments of the present invention and are only used to explain the present invention, not to limit the scope of implementation of the present invention. For those skilled in the art, other implementation methods can certainly be easily made by replacement or modification based on the technical contents disclosed in this specification. Therefore, all changes and improvements made on the principles of the present invention should be included in the scope of the patent application of the present invention.
Claims
1. An inorganic phase-rich double-layer SEI structure, characterized in that: The double-layer SEI structure is in-situ grown on the negative electrode current collector or the metal negative electrode, and includes an inorganic layer and an organic layer, wherein the inorganic layer is located between the negative electrode current collector or the metal negative electrode and the organic layer, and the content of the inorganic layer is greater than that of the organic layer.
2. The inorganic-rich double-layer SEI structure according to claim 1, characterized in that: The cation in the inorganic layer component is Li + Or Na + , the anion is F - , Cl - Br - ,I - , O 2- , S 2- 、Se 2- 、N 3- or P 3- One or more of .
3. A method for regulating the inorganic-rich double-layer SEI structure according to any one of claims 1 to 2 on a metal negative electrode or a negative electrode current collector, characterized in that: The following steps are involved: 1) preparing a slurry containing a terminal group-rich modification material, a binder, and a solvent, and then coating the slurry on a metal negative electrode or a negative electrode current collector to obtain a modified metal negative electrode or a negative electrode current collector; 2) The modified metal anode or anode current collector is used as the working electrode to assemble into a half-cell, and the current density, surface capacity density and cut-off voltage are set for deposition and stripping. During this period, the cations and anions dissociate, desolvate and first react with the organic macromolecules in the electrolyte to form an organic phase. Then, when the battery potential is close to 0 V, the cations reach the metal anode or anode current collector, spontaneously react with the end groups on the modified material and directly generate an inorganic phase in situ on the metal anode or anode current collector, that is, a double-layer SEI structure rich in inorganic phase is formed on the metal anode or anode current collector.
4. The control method according to claim 3, characterized in that: The end group-rich modified material is an end group-rich MXene material, a carbon material or a conductive polymer.
5. The control method according to claim 4, characterized in that: The terminal group is selected from one or more of -F, -Cl, -Br, -I, -O, -S, -Se, -N or -P.
6. A method for activating a negative electrode current collector of a battery based on the inorganic phase-rich double-layer SEI structure according to any one of claims 1 to 2, characterized in that: The following steps are involved: 1) preparing a slurry containing a terminal group-rich modification material, a binder, and a solvent, and then coating the slurry on a negative electrode current collector to obtain a modified negative electrode current collector; 2) The modified current collector is used as the working electrode and assembled into a half-cell. The current density and surface capacity density are set for deposition and stripping. During this period, the cations and anions dissociate, desolvate, and first react with the organic macromolecules in the electrolyte to form an organic phase. Then the cations reach the negative electrode current collector, spontaneously react with the end groups on the modified material, and directly generate an inorganic phase in situ on the negative electrode current collector, thereby forming an inorganic phase-rich double-layer SEI structure on the negative electrode current collector. The activation is terminated when the impedance value of the SEI structure is measured to be unchanged.
7. A lithium metal battery, characterized in that: The metal negative electrode is coated with a modification material rich in end groups, and the inorganic phase-rich double-layer SEI structure described in any one of claims 1 to 2 is generated in situ during the battery cycle test.
8. A negative electrode-free lithium metal battery, characterized in that: The negative electrode current collector is coated with a modification material rich in end groups, and after activation, the inorganic phase-rich double-layer SEI structure described in any one of claims 1 to 2 is generated in situ.
9. A sodium metal battery, characterized in that: The metal negative electrode is coated with a modification material rich in end groups, and the inorganic phase-rich double-layer SEI structure described in any one of claims 1 to 2 is generated in situ during the battery cycle test.
10. A negative electrode-free sodium metal battery, characterized in that: The negative electrode current collector is coated with a modification material rich in end groups, and after activation, the inorganic phase-rich double-layer SEI structure described in any one of claims 1 to 2 is generated in situ.
Citation Information
Cited By
PDA-ZrO2 coated zinc anode, preparation method thereof and battery
CN120998926A
Lithium deposition redirection mixed conductor layer and preparation method thereof and lithium metal battery
CN122599439A